Self-assessment of Readiness and Equipment of Dental Clinics for Managing Medical Emergencies in the Republic of Croatia - Bruno Špiljak; Maja Firić; Miroslav Sikora; Vlaho Brailo (Acta Stomatologica Croatica)
Objective: Medical emergencies (MEs) pose immediate threats to patients’ lives and health and can occur in dental clinics. This study aimed to evaluate how well dentists in Croatia feel prepared to manage MEs and how well their clinics are equipped with necessary drugs and equipment. Materials and Methods: The study involved 319 active dentists who completed an online questionnaire covering demographic data, education on MEs, self-assessment of their ability to manage MEs, clinic equipment for MEs, knowledge and ability to use drugs for MEs, and opinions on further education needs. The normality of the distribution was tested using the Shapiro-Wilk test. Percentages were used for nominal variables, and mean ± standard deviation was applied for continuous variables. A t-test and χ2 test were used to analyze group differences. Results: Most of the respondents (77%) were general dentists. Adrenaline was the most available drug (98.7%), while other drugs were less common. The respondents in secondary and tertiary healthcare clinics showed greater readiness and better education for managing MEs and attended ME training significantly more often than those working in primary healthcare clinics (p=0.009). Additionally, the respondents with specialization and experience in secondary and tertiary clinics had more drugs and equipment and attended ME training more frequently (p < 0.0001 and p=0.001). Conclusions: Training on managing MEs should be held more frequently, on an annual basis, and should be mandatory for all dentists, regardless of their workplace.